Nonprofits and Social Entrepreneurship Intentions: Examining the Role of Organizational Attributes - TAN, Wee Liang (Institutional Knowledge at Singapore Management University, 2011)
Little is known about social entrepreneurship in nonprofits, especially the factors that influence social entrepreneurship intentions of these organizations. This study explores the direct effect of the organizational attributes (commercial experiences of CEO, organizational level of entrepreneurial orientation and collective efficacy, resource availability and social cause) on the nonprofit organization’s intention to start a social enterprise. We find that nonprofits led by CEOs with commercial experience, with high collective efficacy and organization innovativeness are more likely to evince intentions to start a social enterprise. Whilst it might have been thought that the nonprofits’ social causes may have a negative effect on social entrepreneurship, it was found to have a positive influence. Contrary to expectations, resource availability was not significant to intentions; neither was risk-taking. Hence, nonprofit organizations keen to foster social entrepreneurship are advised to seek to align any social entrepreneurship activities to their social causes and develop internal capability for social entrepreneurship and collective efficacy.